2020
DOI: 10.1038/s41467-020-20069-4
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic sequestration of the vitamin D receptor as a therapeutic option for vitamin D-induced hypercalcemia

Abstract: The bioactive vitamin D3, 1α,25(OH)2D3, plays a central role in calcium homeostasis by controlling the activity of the vitamin D receptor (VDR) in various tissues. Hypercalcemia secondary to high circulating levels of vitamin D3 leads to hypercalciuria, nephrocalcinosis and renal dysfunctions. Current therapeutic strategies aim at limiting calcium intake, absorption and resorption, or 1α,25(OH)2D3 synthesis, but are poorly efficient. In this study, we identify WBP4 as a new VDR interactant, and demonstrate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 46 publications
3
14
0
Order By: Relevance
“…To determine the effects of 2 d in vivo, wild type mice were daily treated with various doses of 2 d and 1 for 5 days. In agreement with previous results, [24] 1 μg/kg of 1 induced hypercalcemia and the transcript levels of the vitamin D target genes Cyp24a1 and S100g in the kidney (Figure 3, D-E). However, the renal transcript levels were similar in mice treated with 2 d and with vehicle (Figure 3, D-E).…”
Section: Functional Activitysupporting
confidence: 93%
“…To determine the effects of 2 d in vivo, wild type mice were daily treated with various doses of 2 d and 1 for 5 days. In agreement with previous results, [24] 1 μg/kg of 1 induced hypercalcemia and the transcript levels of the vitamin D target genes Cyp24a1 and S100g in the kidney (Figure 3, D-E). However, the renal transcript levels were similar in mice treated with 2 d and with vehicle (Figure 3, D-E).…”
Section: Functional Activitysupporting
confidence: 93%
“…The docking data were substantially corroborated by the crystal structures of 3a and 3b in complex with zebrafish (z) VDR LBD and a peptide encompassing the second LXXLL motif of NCoA1 solved by X-ray crystallography to a resolution of 2.6 Å. Note that we have previously shown that the binding of 1,25D 3 to zVDR LBD is similar to that of hVDR LBD , and to that of full-length hVDR . The detailed statistics of diffraction data collection and structural refinement are summarized in Table S1.…”
Section: Resultsmentioning
confidence: 67%
“…Note that we have previously shown that the binding of 1,25D 3 to zVDR LBD is similar to that of hVDR LBD 68,69 and to that of full-length hVDR. 70 The detailed statistics of diffraction data collection and structural refinement are summarized in Table S1. Both VDR complexes adopt the active conformation with H12 in agonist position, forming together with helices H3 and H4 the coactivator binding site.…”
Section: ■ Introductionmentioning
confidence: 99%
“…(C) Averaged equilibrium dissociation constants for the interactions of VDR LBDs with the hRXRα LBD from two to three independent experiments. *From ref .…”
Section: Resultsmentioning
confidence: 99%